P271 Effect of extrafine single inhaler triple therapy on lung function and use of rescue medication: results from the trinity study. (15th November 2017) - Scuri, M; Vestbo, J; Papi, A; Corradi, M; Montagna, I; Francisco, C; Cohuet, G; Vezzoli, S; Muraro, A; Petruzzelli, S; Singh, D
Abstract : Rationale: Treatment with extrafine triple therapy in a single inhaler has beneficial effects compared to LAMA monotherapy on lung function and symptoms. This analysis focuses on rescue medication use (as this is associated with symptoms) and lung function responder analysis identifying clinically relevant effects. Methods: In this 52 week multicentre, randomised, double-blind, active-controlled study, 2691 patients with severe to very severe COPD, exacerbations history, and CAT total score ≥10 were randomised (2:2:1) to tiotropium, fixed triple (beclometasone/formoterol/glycopyrronium), or free triple (beclometasone/formoterol+tiotropium). Secondary endpoints included FEV1 responders at week 26 and 52 using different thresholds for response and change from baseline in average use of rescue medication. Results: Both fixed and free triple FEV1 responder percentages were significantly greater than tiotropium at weeks 26 and 52 regardless of the threshold used to define the response (p<0.001 for all analyses). At 26 weeks the proportion of responders were 48.0% (fixed triple) and 48.1% (free triple) for the 50 ml threshold, and 36.7% and 34.8% at the higher 120 mL threshold, with similar Results at week 52. Corresponding FEV1 responder percentages for tiotropium were lower at the 50 mL threshold (35.7% and 34.8%, at weeks 26 and 52 respectively) and 120 mL threshold (25.3% and 24.8%, respectively). In terms of average percentage of days without rescue medication use over 52 weeks, all treatments showed statistically significant increases from baseline which were more marked with fixed and free triple (13.9 [95%CI: 12;15.8] and 14.8% [95%CI: 12.1;17.4] respectively) compared to 5.2% [95%CI: 3.3;7.1] for tiotropium alone (p<0.001) and no difference observed between fixed and free triple with an adjusted mean difference of −0.8% [95% CI: −4.1;2.4] (p=0.616). Average use of rescue medication with both fixed and free triple treatments over 52 weeks compared to tiotropium alone was reduced by 0.6 [95%CI: 0.4;0.7] and 0.6 [95%CI: 0.5;0.8] puffs/day, respectively (p<0.001). Conclusions: Extrafine triple therapy in a single inhaler provides superior clinical benefits in severe to very severe COPD patients in terms of lung function (by individual responder analysis) and rescue medication use compared with tiotropium alone. Please refer to page A260 for declarations of interest in relation to abstract P271.